A model comparing how rapidly transfusion of solvent detergent plasma restores clotting factors versus infusion of albumin-saline. Issue 3 (December 2015) - Jilma-Stohlawetz, Petra; Kursten, Friedrich W.; Horvath, Michaela; Leitner, Gerda; List, Jana; Marcek, Jana; Quehenberger, Peter; Schwameis, Michael; Bartko, Johann; Jilma, Bernd
Abstract: Background: A recent randomized controlled trial demonstrated the bioequivalence between universally applicable and AB0 compatible transfusion plasma in healthy volunteers. There was a limited change in coagulation factor levels and inhibitors before and after plasmapheresis and subsequent plasma transfusion. The aim of this extension trial was to investigate the true capacity of these plasma products to restore baseline levels of coagulation factors and inhibitors after plasma depletion in comparison to haemodilution induced by infusion of albumin solution. Materials and methods: Fourteen healthy subjects, who completed both plasma transfusion periods, underwent an additional plasmapheresis (600 mL) followed by an infusion of 1200 mL albumin (3.125%) in a third period. Results: The fibrinogen levels, as well as other clotting factors (FII, FV, FVII and FXI), decreased by 10% after plasmapheresis, and subsequent infusion of albumin solution further aggravated this drop in clotting factors to approximately 20–25%. The clotting factors with a long half-life were not even restored 24 hours after infusion of albumin solution, whereas those with a short half-life were replenished by endogenous synthesis within 24 hours. In contrast, transfusion of either plasma product rapidly restored all clotting parameters and inhibitors (protein S and plasmin inhibitor) immediately after transfusion. Conclusion: This study demonstrates that albumin solution induces an enhanced dilution of clotting factors and inhibitors, whereas both plasma products quickly compensated for the experimental loss of these plasma proteins.